PROBLEMATIKA PEMBELAJARAN BAHASA ARAB BAGI MAHASISWA TUNANETRA DI FAKULTAS ILMU TARBIYAH DAN KEGURUAN UIN SUNAN KALIJAGA - Muhammad Jafar Shodiq (CMES (Center of Middle Eastern Studies), 2014)
Until now, the fulfillment of education‟s rights of disabilities has been done by many educational institutions, including UIN Sunan Kalijaga Yogyakarta. As the onlyuniversity‟s inclusion in Indonesia, UIN Sunan Kalijaga Yogyakarta could be a model forother universities in terms of services to the disabled. However, did the service provideby UIN Sunan Kalijaga is completely inclusion? How is the implementation of learningactivities which form the core of education? This paper aims to describe the problems ofArabic learning for visually impaired students in the Faculty of Tarbiyah and TeachingUIN Sunan Kalidjaga Yogyakarta.